Gold-catalyzed intermolecular hydroamination of allenes with sulfonamides - Zhang, Chen; Zhang, Shao-Qiao; Cai, Hua-Jun; Cui, Dong-Mei (Beilstein Journal of Organic Chemistry, 2013)
A co-catalyst of (PPh3)AuCl/AgOTf for the intermolecular hydroamination of allenes with sulfonamides is shown. The reaction proceeded smoothly under mild conditions for differently substituted allenes giving N-allylic sulfonamides in good yields with high regioselectivity and E-selectivity.
Keywords: allene; gold catalysis; hydroamination; N-sulfonyl; selectivity; sulfonamide